2013
DOI: 10.1016/j.molcel.2013.08.021
|View full text |Cite
|
Sign up to set email alerts
|

The Dependence Receptor TrkC Triggers Mitochondria-Dependent Apoptosis upon Cobra-1 Recruitment

Abstract: The neurotrophin receptor TrkC was recently identified as a dependence receptor, and, as such, it triggers apoptosis in the absence of its ligand, NT-3. The molecular mechanism for apoptotic engagement involves the double cleavage of the receptor's intracellular domain, leading to the formation of a proapoptotic "killer" fragment (TrkC KF). Here, we show that TrkC KF interacts with Cobra1, a putative cofactor of BRCA1, and that Cobra1 is required for TrkC-induced apoptosis. We also show that, in the developing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 48 publications
(76 reference statements)
0
34
0
Order By: Relevance
“…Apoptosis and autophagy, two methods for programmed self-destruction of cells, have long been topics of investigation by the research community. 8 Apoptosis, also known as type I cell death, is one of the best-described types of programmed cell death (PCD), and it activates cellular death signaling cascades such as mitochondria-dependent and death receptor-mediated signaling, 9 , 10 which are followed by nuclear chromatin condensation and nuclear fragmentation. 11 In contrast, autophagy is an intracellular self-catabolic degradation process.…”
Section: Introductionmentioning
confidence: 99%
“…Apoptosis and autophagy, two methods for programmed self-destruction of cells, have long been topics of investigation by the research community. 8 Apoptosis, also known as type I cell death, is one of the best-described types of programmed cell death (PCD), and it activates cellular death signaling cascades such as mitochondria-dependent and death receptor-mediated signaling, 9 , 10 which are followed by nuclear chromatin condensation and nuclear fragmentation. 11 In contrast, autophagy is an intracellular self-catabolic degradation process.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a comparison of TrkA −/− and NGF −/− mutant mouse embryos revealed that deletion of TrkA protects NGF-dependent E11.5 DRG neurons from death in vivo (Nikoletopoulou et al, 2010). Current findings suggest that the death-promoting effect of dependence receptors in the PNS involves complex interactions with p75 and possibly the generation of proapoptotic receptor fragments (Dekkers et al, 2013; Ichim et al, 2013; Nikoletopoulou et al, 2010; Tauszig-Delamasure et al, 2007). Notably, the sensory and sympathetic neuron loss in E13.5 TrkA −/− mutants can be significantly rescued by simultaneous inhibition of p75 NTR (Majdan et al, 2001; Nikoletopoulou et al, 2010).…”
Section: Trophic Signaling Mechanisms During Pns Developmentmentioning
confidence: 85%
“…Intriguingly, dependence receptors promote cell survival, proliferation and differentiation in physiological conditions (when their cognate ligands are normally available), but activate distinct (and not completely elucidated) lethal signaling cascades (generally impinging on caspase activation) once ligand availability falls below a specific threshold level [ 350 ]. Thus, in the absence of their respective ligands: (1) DCC is cleaved by CASP3 and this promotes its association with adaptor protein, phosphotyrosine interacting with PH domain and leucine zipper 1 (APPL1) and CASP9, resulting in the activation of the CASP9-CASP3 cascade [ 350 , 351 ]; (2) PTCH1 interacts with the cytosolic adaptor four and a half LIM domains 2 (FHL2; best known as DRAL), hence favoring the assembly of a CASP9-activating complex consisting of caspase recruitment domain family member 8 (CARD8; also known as TUCAN) and neural precursor cell expressed, developmentally down-regulated 4, E3 ubiquitin protein ligase (NEDD4) [ 352 354 ]; (3) UNC5B enables the protein phosphatase 2 (PP2A)-mediated activating dephosphorylation of death associated protein kinase 1 (DAPK1), which is known to promote p53-dependent RCD [ 355 357 ]; and (4) UNC5D and NTRK3 are subjected to CASP3 cleavage generating intracellular fragments that translocate either into the nucleus to trigger the E2F transcription factor 1 (E2F1)-driven expression of pro-apoptotic genes (as in the case of UNC5D) or at mitochondria to activate CASP9 upon MOMP (as in the case of NTRK3) [ 358 , 359 ].…”
Section: Extrinsic Apoptosismentioning
confidence: 99%